2022
DOI: 10.3390/powders1030011
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Microfluidic Synthesis of Solid Catalysts

Abstract: Heterogeneous catalysis plays a central role in the chemical and energy fields, owing to the high and tunable activities of solid catalysts that are essential to achieve the favorable reaction process efficiency, and their ease of recycle and reuse. Numerous research efforts have been focused on the synthesis of solid catalysts towards obtaining the desired structure, property and catalytic performance. The emergence and development of microfluidic reactor technology provide a new and attractive platform for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Additionally, reactants and catalysts can be used in smaller quantities, effectively enabling the screening of a variety of reaction conditions with just small amounts of reagents and catalysts. Numerous studies have demonstrated the benefits of adopting microdroplet technology over batch operations in wet chemical catalysis [11–13] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, reactants and catalysts can be used in smaller quantities, effectively enabling the screening of a variety of reaction conditions with just small amounts of reagents and catalysts. Numerous studies have demonstrated the benefits of adopting microdroplet technology over batch operations in wet chemical catalysis [11–13] …”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the benefits of adopting microdroplet technology over batch operations in wet chemical catalysis. [11][12][13] Due to its continuous working mode, superior mixing efficiency, and well-controlled residence time, microdropletbased catalytic technology is facile, versatile, and reproducible. [14] While conventional batch reactors typically require hours or days to complete a catalytic reaction, microdroplets typically require only seconds to tens of minutes.…”
Section: Introductionmentioning
confidence: 99%